Wage mobility in Austria 1986 - 1996 - Helmut Hofer; Andrea Weber (Institute for Advanced Studies (IHS), 2001)
We examine wage mobility of Austrians, using 1986-1996 data from administrative sources. For the evaluation of wage mobility we calculate mobility measures based on transitions between quintiles in the wage distribution. A second group of indices measure wage mobility by the extent to which averaging wages over a longer period decreases cross sectional inequality. We find that mobility reduces wage inequality by 7 per cent over a six-year period. This equalising effect of wage mobility is only half as large as in other OECD countries. Considering an 11 year horizon for Austria implies a reduction of inequality of 10 per cent. Mobility is high only for young workers and for workers who changed their employer at least once during the observation period. Decomposing the sample into sex, age and worker-type groups and comparing within- and between-group mobility shows that most of the equalising effect of mobility occurs within the groups.
Keywords: J6; J31; P52; 330; wage mobility; Shorrock's indices; corporatism; Lohnstruktur; Arbeitsmobilität; Österreich